Registration frameworks for aligning brain images - Bravo Valero, Antonio José; Vera, Miguel Ángel; Huérfano, Yoleidy Katherine (AVFT – Archivos Venezolanos de Farmacología y Terapéutica, 2020)
In this paper, the results obtained by the registration process of brain image volumes obtained by magnetic resonance imaging (MRI) and functional magnetic resonance imaging (fMRI) using two different computational frameworks are presented. The objective is to compare the performance of each framework, focusing this comparison in the error measurement obtained by brain volumes registration. The comparison involves the intra patient and intra modality (MRI–MRI and fMRI–fMRI) registration. Statistical Parametric Mapping (SPM) and Insight Segmentation and Registration Toolkit (ITK) are chosen as registration frameworks. The proposed methodology considers the data sets generation, test planning, designing test cases, tests execution and evaluating. Finally, these results are analysed. The correspondence between the volumes registered and the target volume using the ITK framework is greater than that obtained with the SPM framework.